(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
In this paper, a kind of microcapsule containing phase change material of n-octadecane was successfully synthesized based on in situ polymerization where trimethylol melamine and hexamethylol melamine were shell materials. We used different emulsification time, reaction time and different treatment to improve the quality of the microcapsules. The microcapsule and coated fabric were characterized by the optical microscope, Scanning Electronic Microscope (SEM), laser diameter distribution machine and Differential Scanning Calorimeter (DSC). The optical microscope and SEM pictures showed that this microcapsule has good surface configuration. Particle size with laser diameter distribution machine displayed that grains of the microcapsule were distributed evenly. The DSC results revealed the phase- changing temperature and enthalpy of the microcapsule.